Politik Hukum Agraria Pada Tanah Ulayat - I Nyoman Prabu Buana Rumiartha (Magister Hukum Pascasarjana Univeristas Ngurah Rai, 2019)
The responsive character of Law Number 5 of 1960 concerning Basic Regulations on the Principles of Agrarian Law is reflected in the norms contained in Article 5. The politics of agrarian law on customary land also refers to Article 18B paragraph (2) of the 1945 Constitution which emphasizes: